2022
DOI: 10.1146/annurev-cellbio-120420-095337
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Principles of Spatial and Temporal Patterns in Cells and Tissues

Abstract: Patterns are ubiquitous in living systems and underlie the dynamic organization of cells, tissues, and embryos. Mathematical frameworks have been devised to account for the self-organization of biological patterns, most famously the Turing framework. Patterns can be defined in space, for example, to form stripes; in time, such as during oscillations; or both, to form traveling waves. The formation of these patterns can have different origins: purely chemical, purely mechanical, or a combination of the two. Bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 214 publications
0
18
0
Order By: Relevance
“…Living systems exhibit patterns at different length scales depending on the mechanism driving their organization. The most prevalent mechanisms are diffusion-based biochemical pattern formation, such as Turing patterns, and various mechano-chemical patterns 49 . Here, we demonstrate the existence of an emergent length scale based on coupling between mechanics, turnover and geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Living systems exhibit patterns at different length scales depending on the mechanism driving their organization. The most prevalent mechanisms are diffusion-based biochemical pattern formation, such as Turing patterns, and various mechano-chemical patterns 49 . Here, we demonstrate the existence of an emergent length scale based on coupling between mechanics, turnover and geometry.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, signaling waves have emerged as a common mechanism for the regulation of developmental processes 21,25,30 . Waves can facilitate the rapid propagation of biochemical signals and help organize cellular responses across large tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Our experimental frameworks are suitable to explore how enhancers mediate dynamic gene expression in an unbiased fashion. However, in this work we set to test a specific model: the ‘Enhancer Switching model, a scheme some of the authors have recently suggested (23,34) to elucidate how gene expression waves, a phenomenon commonly observed during embryonic development (6,82,83), are generated at the molecular level. The model predicts that each patterning gene is simultaneously wired into two gene networks: (i) a dynamic network that drives sequential or periodic gene activities, and (ii) a static network that stabilizes gene activities into gene expression domains.…”
Section: Discussionmentioning
confidence: 99%
“…We also developed an enhancer reporter system in Tribolium able to visualize dynamic transcriptional activities in both fixed and live embryos ( Figure 3 ). Both our enhancer discovery and activity visualization systems are efforts to establish the AP patterning in Tribolium as a model system for studying dynamic gene expressions, especially gene expression waves, a phenomenon commonly observed during embryonic development (9,10,109). Although our experimental framework is suitable for exploring how enhancers mediate dynamic gene expression in an unbiased fashion, we set in this work to test the plausibility of a specific model: the ‘Enhancer Switching’ model ( Figure 1 ), a scheme some of the authors have recently suggested (31,49) to elucidate how gene expression waves are generated at the molecular level.…”
Section: Discussionmentioning
confidence: 99%